DOMINASI FDI SINGAPURA DAN RIVALITAS STRUKTURAL DALAM RELASI EKONOMI INDONESIA-SINGAPURA DI BAWAH AEC - Rafli Zahran Siregar; Mhd. Suhaidi; Fakhri Ahmad; Fasha Rahmadhani Syafitri; Laura Anna Lusia Manullang (CV. Denasya Smart Publisher, 2026)
This article examines the dynamics of the bilateral economic relations between Indonesia and Singapore within the framework of the ASEAN Economic Community (AEC), focusing on three main dimensions: the structural asymmetry of both countries' economic capacities, the pattern of Indonesia's dependence on Singapore's foreign direct investment (FDI), and the rivalry of interests operating beneath the surface of bilateral cooperation narratives. Employing a qualitative approach with a case study design and secondary data analysis covering the period 2015–2024, this article finds that the bilateral relationship is characterized by asymmetric interdependence that has deepened over the course of AEC implementation. Singapore's FDI dominance, growing from USD 5.9 billion in 2015 to USD 20,1 billion in 2024 and accounting for 52 percent of Indonesia's total FDI inflows, reflects a profound structural dependency. Rather than functioning as a mechanism for economic convergence, the AEC has reinforced pre-existing asymmetric investment patterns, as formal liberalization has not been accompanied by adequate redistributive mechanisms. This article argues that a transformation toward a more balanced relationship requires Indonesia to strengthen its domestic institutional capacity, diversify its sources of investment, and leverage its strategic assets more effectively in both bilateral and regional multilateral forums.